Analisis Faktor-Faktor yang Mempengaruhi Kinerja Usaha Kecil di Kota Pare-Pare - Muhammad Rakib (Jurnal Aplikasi Manajemen, 2012)
The purpose of this study was to analyze the entrepreneurship communication factor, entrepreneurship learning and attitude toward small business performance. This study took a sample of 140 small business owners in the town of Pare Pare using questionnaires, observation, interviews, and documentation to collect data. The data analysis technique used is Structural Equation Modeling (SEM). The findings showed that communication factor entrepreneurship, entrepreneurial learning and entrepreneurial attitude significantly influence the performance of small businesses. This leads to the implication that to predict the performance of small business formation should be taken into account the amount of communication variables entrepreneurship, entrepreneurial learning and entrepreneurial attitude either partially or simultaneously, and the contribution of these variables on the performance of small businesses providing real significance, either partially or simultaneously. Based on these findings it is suggested to: (1) The Policy-makers (Government); for the development of small businesses not only conducted with the provision of venture capital, but combined with human resource development so as to obtain a quality selfemployment, (2) Small Business Owners (Entrepreneurial) ; to equip themselves with techniques to communicate effectively, improve product quality through the study of entrepreneurship, and develop their entrepreneurship attitude , (3) Manufacturer Education Curriculum; for economic education has a mission of implementing entrepreneurship education, then it is proper curriculum and learning strategies or changes adjustment, started revising material entrepreneurship, especially in formal education (schools), and (4) Researcher; need to assess the external factors affecting the performance of small businesses, expand the research variable indicators, developed with quantitative approach, and assess the small business at large.Keywords: communications entrepreneur, entrepreneurial learning, entrepreneurial attitude, and performance of small businesses